A simple JPEG-LS compressed technique for 2DGE image with ROI emphasis. (February 2015) - Chen, J.; Chen, T-S.; Lin, C.; Chen, S-Y.; Lin, J.
Abstract : In this paper, we proposed a JPEG-LS lossless region of interest compression scheme to compress images to smaller sizes and to preserve the significant protein data. The scheme involved manipulating NEAR of JPEGLS to compress the protein spots (ROI) in lossless mode and the non-ROI (unimportant) areas in lossy. Experimental results showed smaller size compressed 2D gel electrophoresis (2DGE) image, which can be recovered for its lossless ROI protein spots. The scheme can also be used to customise the size of compressed image by proportionally sacrificing the quality of the non-ROI areas of the image. The size to decrease would depend on the relative degree of distortion in the non-ROI that is acceptable to the user while the ROI protein spots remained undistorted.